Remote sensing for geoscientists : image analysis and integration - Prost, G. L. (CRC Press, 2014)
"The third edition of this text has a new title. The previous "Remote Sensing for Geologists: a Guide to Image Interpretation," is now "Remote Sensing for Geoscientists: Image Analysis and Integration." The title change reflects 1) that this edition applies to a broad spectrum of geosciences, not just geology, 2) that remote sensing has become more than photointerpretation, and 3) an emphasis on integration of multiple remote sensing technologies to solve Earth science problems. Since publication of the 2nd edition in 2001, remote sensing systems have been acquiring not only visible, infrared, and microwave images, but also have been detecting atmospheric gases, ocean temperatures, wind speeds, and mapping minerals on the Moon and planets, as well as recording potential fields and digital elevation data"--